EVALUASI KEBIJAKAN PELAYANAN IZIN REKLAME PADA BADAN PELAYANAN PERIZINAN TERPADU (BP2T) KOTA MANADO - Sutriyanti, Lilys; Mandey, Jantje; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: Background: The public service as any service, either in the form of public goods and publicservices that, in principle, be the responsibility of central or local government agencies in an effort to meetthe needs of the community or the implementation of the provisions of the legislation. Integrated one-stopservice is one of the government's efforts in improving the quality of public services particularly related tolicensing services. Quality of service required permission billboards as one of the factors that drive thesuccess of a particular company to improve its business. Methods: Using qualitative research methodswith the aim of this study was to evaluate the results of policies permit services advertisement onIntegrated Licensing Service Agency of Manado. Data collection techniques in this study throughobservation or field notes directly to the location of research, conduct interviews and documentation.Discussion: The results of the evaluation showed that service policies permit billboards in BP2T has notbeen equally effective because there are still some things that are not as it should be such a lack ofcoordination with the technical team, the level of satisfaction is not maximized, the realization of thetargets which have not been optimal, human resources are still less . Conclusions: Policy billboard permitservices already shown good results but not maximum so there is still room for improvement for the nextyear so that the results achieved can be maximized.Keywords: Evaluation of Public Policy, Permit Services Advertising.